Design of Project Risk Management to Mitigate Project Delay in the Onshore Construction Industry - Firdaus Yusri Muhammad; Gatot Yudoko; Muhammad Hanafi (Journal of Business, Social and Technology, 2025)
Background: Project delays remain a critical issue in the land-based construction industry, often leading to financial losses and missed business opportunities, particularly under lump-sum contract schemes. The coastal protection project undertaken by PT Sabar Sejahtera experienced a three-month delay, indicating weaknesses in risk management practices during the early stages of the project. Aims: This study aims to design a structured project risk management system to mitigate schedule delays in land-based construction projects through a case study of the PT Sabar Sejahtera coastal protection project. Methods: A mixed-method approach combining qualitative and quantitative techniques was employed. Primary data were collected through focus group discussions (FGDs) with key project stakeholders, while secondary data were obtained from internal company documents. Root cause analysis was conducted using a Current Reality Tree (CRT) to identify the main causes of project delays, and proposed solutions were developed using a Future Reality Tree (FRT). Risk evaluation was performed using Failure Mode and Effects Analysis (FMEA) to calculate the Risk Priority Number (RPN), supported by the application of a project risk management framework based on the PMBOK 6th Edition. Result: The findings indicate that the primary causes of project delays were systematic errors during the tendering and planning stages, as well as the absence of a formal risk mitigation plan. These factors generated a domino effect that adversely affected procurement processes, equipment availability, project scheduling, and the main contractor’s confidence. Conclusion: The study concludes that implementing an integrated and comprehensive risk management system from the early stages of a project is essential to prevent similar delays in the future. Enhancing tendering and planning processes through early cross-departmental involvement and applying the full PMBOK risk management cycle can significantly improve project efficiency and control in complex construction environments.